Prove &#x2211;<!-- ∑ --> <mrow class="MJX-TeXAtom-ORD"> 1 ( x

Ellie Benjamin

Ellie Benjamin

Answered question

2022-07-05

Prove 1 ( x + 2 y ) 2 1 x y + y z + z x
Let x , y , z > 0 Prove that:
1 ( x + 2 y ) 2 + 1 ( y + 2 z ) 2 + 1 ( z + 2 x ) 2 1 x y + y z + z x
I tried to apply Cauchy - Schwarz's inequality but I couldn't prove this inequality!

Answer & Explanation

gozaderaradiox5

gozaderaradiox5

Beginner2022-07-06Added 19 answers

a = x + 2 y , b = y + 2 z , c = z + 2 x x = a 2 b + 4 c 9 , y = b 2 c + 4 a 9 , z = c 2 a + 4 b 9
the inequality become:
1 a 2 + 1 b 2 + 1 c 2 27 5 ( a b + b c + a c ) 2 ( a 2 + b 2 + c 2 )
now use UVW method:
3 u = a + b + c , 3 v 2 = a b + b c + a c , w 3 = a b c u v w
( 3 v 2 ) 2 6 u w 3 w 6 3 3 v 2 2 u 2 w 6 + 2 u ( 3 v 2 2 u 2 ) w 3 3 v 4 ( 3 v 2 u 2 ) 0
let w 3 = x , f ( x ) = x 2 + 2 u ( 3 v 2 2 u 2 ) x 3 v 4 ( 3 v 2 2 u 2 )
2 u ( 3 v 2 2 u 2 ) 0
f m a x ( x ) = f ( w 3 | w = v ) = f ( v 3 ), when
w = v u = v = w f ( v 3 ) = 0 f ( x ) 0
when u = v = w a = b = c x = y = z
QED.

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?